Preparation of a Pressure Sensitive Adhesive (PSA) with the ZnO Nanoparticles Incorporation. Study of its Physicochemical and Antimicrobial Properties - Ramírez-Barrón, S. N.; Sánchez-Valdés, S.; Puente-Urbina, B. A.; Martínez-Montemayor, S.; Esparza-González, S. C.; Betancourt-Galindo, R. (Revista Mexicana de Ingenieria Biomedica, 2018)
The process for obtaining a pressure sensitive adhesive (PSA) is described. This PSA is formed by an acrylate copoly-mer of 2-ethylhexyl (2-EHA) / methyl methacrylate (MMA) in an 80:20 ratio which was polymerized by emulsion polymerization technique. Zinc oxide nanoparticles (NPZnO) were added to this copolymer, which were previously synthesized, and surface modified with 3-aminopropyltretoxysilane (APTES) and dimethyl sulfoxide (DMSO) to improve its dispersion in the copolymer matrix. The obtained nanocomposites were characterized by infrared spec-troscopy (FTIR), differential scanning calorimetry (DSC) and T-peel adhesion tests. In addition, the antimicrobial activity against S. aureus and S. pyogenes as well as the cytotoxicity in human cells (HeLa) were determined. The results demonstrated that the ZnO nanoparticles incorporation enhanced the glass transition temperature (Tg) and the antimicrobial activity of PSA copolymer as well as its surface adhesion. It was confirmed that NPZnO modifi-cation with APTES increased its antimicrobial activity. Regarding adhesive behavior, PSA with unmodified NPZnO showed a greater peel resistance. This indicates that these nanoparticles enhances the cohesive force and induces a better high temperature performance, which is beneficial for the final application. Finally, cytotoxicity results showed that the incorporation of NPZnO to PSA decreases the cell viability, however this PSA is not toxic according to the standard ISO 10993 test for in vitro cytotoxicity.